Excavations at South Glendale (Scottish Historical and Archaeological Internet Reports, 2003)
Details of site location, topographical survey, site history and a nearby cairn are presented. Two areas were excavated. Area I contained pits, a hearth, paving stones and stakeholes suggestive of settlement. Area 2 contained the remains of a post-medieval byre overlying midden and cultivation deposits.